Analisis Kinerja Operasi Jaringan Transportasi Pipa Gas dalam Mendukung Pasokan Gas Alam di Grissik-Duri pada PT Transportasi Gas Indonesia - Yoferdi, Faridz; Chandra, Yehoshua (Jurnal Sistem Transportasi & Logistik, 2023)
The pipeline transportation network is an efficient mode of transport that facilitates the delivery of natural gas supplies from one region to another. The risk of leaks has become a serious issue in the transportation of natural gas through pipelines. Leaks can occur due to various factors such as corrosion, mechanical damage, or operational errors. Therefore, the transporter must ensure that every operational activity runs according to the procedures. This research aims to analyze the optimization of pipeline network performance. The main objective is to understand the operational performance of the gas pipeline network at PT Transportasi Gas Indonesia in delivering gas supply in Grissik-Duri. The analysis method used is qualitative descriptive to present an objective description of a condition, starting from data collection, interpretation, to the presentation of the results. Over the past three years, there has been a significant increase in gas delivery volume, namely 273.9 MMSCFD in 2021, 287.2 MMSCFD in 2022, and 291.04 MMSCFD in 2023. The performance of the pipeline network over the last three years has exceeded the established targets, which were 256 MMSCFD in 2021, 276 MMSCFD in 2022, and 279 MMSCFD in 2023. From the results of this research, it can be concluded that the operational performance of the pipeline network shows consistent improvement each year, both in terms of actual volume and capacity utilization. Based on the available data, the operational performance of the pipeline network has been realized effectively and optimally.